Immediate-release tablet formulation of rebamipide and a pharmacokinetic study in healthy human subjects - Won, Yong-Hoon; Goo, Yoon Tae; Sin, Gi Hyeong; Hong, Sun Ho; Kim, Chang Hyun; Kim, Min-Ju; Lee, Tae Hwa; Choi, Young Wook (International journal of clinical pharmacology and therapeutics, 2023)
To develop an immediate-release tablet preparation containing rebamipide (RBM) and perform the bioavailability assessment in the healthy human subjects. Raw RBM powder was characterized using differential scanning calorimetry, powder X-ray diffraction, and scanning electron microscopy (SEM). RBM tablets were manufactured by the wet granulation method, and their dissolution behavior was compared with the reference tablet (Mucosta). A phase I study (n = 47; sequence-randomized, open-label, single-dose, and two-way cross-over design) was designed for oral administration of a test formulation (F4) and Mucosta to healthy human male subjects, and pharmacokinetic parameters including the maximum plasma concentration (C ) and area under the curve from 0 to 12 hours (AUC ) were compared. RBM powder had a multimodal size distribution with typical crystallinity, and the needle-like and elongated morphologies of RBM were visualized using SEM. Various tablet formulations (F1 - F6) were successfully manufactured using wet granulation method. F4 formulation was selected based on the dissolution profile most equivalent to that of Mucosta. F4 was stable for 6 months under accelerated and long-term storage conditions. Based on one-way analysis of variance, the AUC (F(1,92) = 2.40, p = 0.13) and t (F(1,92) = 0.04, p = 0.85) were not significantly different; however, the C (F(1,92) = 5.45, p = 0.022) showed significant difference between F4 and reference tablets. Despite similar in vitro dissolution profiles, in vivo pharmacokinetic results revealed a partial difference between F4 and reference tablets. Thus, further study on formulation development is still needed.